How a woman's myomectomy saved her father's life: evidence of fumarate hydratase-deficient uterine leiomyoma and early detection of germline variants in fumarate hydratase - Greysha Rivera-Cruz, M.D; Baris Boyraz, M.D., Ph.D; John C. Petrozza, M.D (Elsevier, 2022)
Objective: To describe a case of a personal and family history of early uterine leiomyomatosis that revealed a pathogenic variant in the FH gene encoding fumarate hydratase. After the patient's diagnosis, a first-degree relative was detected with early-stage renal cell carcinoma. The patient decided to undergo preimplantation genetic testing to reduce the risk to her future children. Design: A case report of autosomal dominant hereditary leiomyomatosis and renal cell cancer syndrome where the patient underwent 2 cycles of in vitro fertilization with preimplantation genetic testing for monogenic disease/aneuploidy (PGT-MA) that resulted in 3 unaffected, euploid embryos. Setting: Large academic single-center hospital. Patient(s): A 35-year-old nulligravida woman with a personal history of an early-onset uterine leiomyomatosis and a family history of renal cell carcinoma and uterine leiomyomas, who is heterozygous for a pathogenic variant in FH and diagnosed with hereditary leiomyomatosis and renal cell cancer syndrome. Informed consent was obtained. Intervention(s): Two laparoscopic myomectomies were performed, and tissue was sent for histopathology and immunostaining. Hereditary leiomyomatosis and renal cell cancer syndrome was confirmed by germline testing, and 2 cycles of PGT-MA were performed. Main Outcome Measure(s): Through PGT-MA, the patient was able to mitigate the risk of passing a known familial variant to her future children. Result(s): After 2 cycles of in vitro fertilization with PGT-MA, 3 unaffected embryos were available for transfer. An unaffected, euploid embryo was transferred for pregnancy, and the patient is currently pregnant in her second trimester. Conclusion(s): Pathogenic variants in FH should be suspected in patients with early-onset uterine leiomyomas and a family history of cutaneous and/or uterine leiomyomas. Familial variant testing is crucial in identifying relatives at risk to start early screening.